2017
DOI: 10.1080/09640568.2017.1333408
|View full text |Cite
|
Sign up to set email alerts
|

Integrating nature-based tourism and forestry in private lands under heterogeneous visitor preferences for forest attributes

Abstract: Developing nature-based tourism in private lands calls for new mechanisms to consolidate the interests of the tourism industry, visitors, and landowners. This choice experiment study elaborates on the heterogeneity of visitors' preferences and willingness to pay (WTP) for enhanced forest amenities and ecosystem services. The survey, targeting domestic and foreign tourists visiting the Ruka-Kuusamo area in Finland, considered four attributes: landscape quality, outdoor routes, forest biodiversity, and carbon se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Nature-based tourism is a rapidly expanding sector within tourism in Europe [95]. Thus, AFS can improve the rural economy in Europe if management through agritourism and local engagement is supported [96].…”
Section: Recreation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Nature-based tourism is a rapidly expanding sector within tourism in Europe [95]. Thus, AFS can improve the rural economy in Europe if management through agritourism and local engagement is supported [96].…”
Section: Recreation and Culturementioning
confidence: 99%
“…Thus, AFS can improve the rural economy in Europe if management through agritourism and local engagement is supported [96]. Since the aesthetic and recreation values are crucial to the success of ecotourism, there is a need for a market-based contractual mechanism to promote recreation and ecotourism that ensures a high aesthetic and recreational value [95]. Fortunately, some of the fundamental features of AFS have a high aesthetic value.…”
Section: Recreation and Culturementioning
confidence: 99%
“…In the contract, specific forest management practices are defined that allow and support the user of the forest to successfully perform its business activities. By taking into account both visitors' willingness to pay and private landowners' perceived costs of provision Mäntymaa et al (2018a) assessed that the LRVT initiative could be promising in the Ruka-Kuusamo area in northeasten Finland.…”
Section: Background and Literature Review 21 Forests As An Operationmentioning
confidence: 99%
“…Funds for compensating these measures would be collected from the visitors and/or tourism entrepreneurs using the area. The preconditions, demand and supply for launching such a new, market-based mechanism have been studied regarding privately owned forests: Tyrväinen et al (2014b) and Mäntymaa et al (2018a) examined visitors' attitudes and willingness to pay for better quality of the environment, and Mäntymaa et al (2018b) studied forest owners' attitudes to and compensation claims for the suggested payment mechanism. The attitudes of tourism entrepreneurs and their willingness to contribute to funding, however, have not been previously studied on state owned lands.…”
Section: Introductionmentioning
confidence: 99%
“…Narrowing the gap between annual growth and drain via increased industrial wood use would slow down the ongoing development of forest structure, especially the rapid increase of large-sized trees. This would be an unwelcome change from the perspective of preserving biodiversity (Hyvärinen et al 2019) and the recreational use of forests (Mäntymaa et al 2018). Replacing fossil fuels with renewable energy involves additional pressure for increased use of wood fuels and, consequently, forest resources.…”
Section: The Outlook Of Forests Resources In Finlandmentioning
confidence: 99%